Dharma as a practical study of dying. A contribution to the study of the foundations of Buddhist mysticism - Kosior, Krzysztof (Filozofia Chrześcijańska, 2021)
Inspired by the Platonic defi nition of philosophy as preparation for death, the author sketches the way indicated by the Buddha (dharma) as an action aimed at ending the elementary circumstances of life. In addition, he tries to show that despite interpretative controversy and changing cultural context, this action is reproduced in the history of Buddhism. So it has solid, unchanging foundations. To make his reasoning clear, the author explains the key concepts present in Buddhist doctrine: dharma, kamma (karman) and skilful means (upaya kauśalya).